Human centred manufacturing: methodology for ergonomic previsional evaluation of manual assembly operations - Di Pardo, Massimo; Monferino, Rossella; Spada, Stefania; Costantino, Marco (Cranfield University Press, 2013)
The challenge of flexibility and productivity for manufacturing operations needs a new concept based on “human-centered manufacturing process”. This concept must consider basically the ergonomics of workplaces and workload balancing. The application of this concept is achievable through the detailed knowledge of the interaction between human and workplace, in particular as far as the mechanical load (or work load) arising from product design and from manufacturing process definition (included tools and equipment). The measurement of workload then is a fundamental for new (and existing) workplaces. In this paper is described the methodology that considers the procedure and instruments for measuring ergonomic parameters and the use of EAWS method to assess the ergonomic risk level of the workplace summarized by a score. EAWS considers postural aspects and dynamics of work activity. Design or modification of the workplace can be defined on base of the results obtained by the methodology application.
Keywords: Manufacturing; Ergonomics; Human-Machine Interaction